Decay mechanism of postharvest pathogens and their management using non-chemical and biological approaches - Kumar, Ritesh; Ghatak, Abhijeet; Balodi, Rekha; Bhagat, Arun P (Journal of Postharvest Technology, 2017)
Ripening is a physiological process that involves numerous biochemical changes including change in sugar composition and change in pH of  the fruit and vegetable tissues. These changes attract a variety of pathogens causing decay, thereby leading to losses up to 25-50% in  harvested crops. The infection by the postharvest pathogens may remain quiescent during fruit or vegetable growth due to unfavourable  growth conditions for pathogen’s development to pathogenesis. Owing ripening and senescence the pathogen transform to necrotrophs,  activation of the pathogen is primarily due to change in pH and cause typical decay symptoms. Some pathogens have developed a mechanism for altering the pH of host environment (tissue), thereby increasing virulence. The postharvest pathogens cause acidification by  producing organic acids and alkalization by ammonification of host tissues. Management of postharvest tissue-decaying pathogens is usually  performed by use of fungicides but due to raised environmental concerns and residual effects of fungicides on health alternative management  strategies are required. This approach should be eco-friendly; the use of plant extract and biological agents are in limited use. Thus, it should  be emphasized that management of postharvest food commodity (particularly those of direct consumption like fruit) pathogens can be  achieved by altering the physiological environment and use of alternative management strategies to reduce the residual effect of inorganic  fungicides and other chemicals. This review deals the both of the aspects and encourages the wide use of biorational and biological  approaches for management of postharvest pathogens.
Keywords: biocontrol; decay mechanism; pathogen,; plant extract; postharvest